2016
DOI: 10.18849/ve.v1i3.32
|View full text |Cite
|
Sign up to set email alerts
|

Supraspinatus Tendinopathy in 327 Dogs: A Retrospective Study

Abstract: Objective: To report clinical findings and treatments for dogs with supraspinatus tendinopathy (ST).Background: ST is a term used to describe tears, calcifying tendinopathy, tendinosis and/or injuries in and around the tendon of the supraspinatus muscle, and is a cause of forelimb lameness, especially in sporting and performance dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…8 Supraspinatus tendinopathy is frequently diagnosed in dogs, especially working dogs and dogs used for sport, and cruciate ligament ruptures are common and often bilateral among medium-to large-sized dogs. 9,10 Similar to those in human patients, all of these injuries cause chronic pain and carry a poor prognosis without costly advanced treatments or surgery. These injuries can lead to retirement from work/athletics and possibly euthanasia in veterinary patients.…”
Section: The Clinical Importance Of Tendon and Ligament Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Supraspinatus tendinopathy is frequently diagnosed in dogs, especially working dogs and dogs used for sport, and cruciate ligament ruptures are common and often bilateral among medium-to large-sized dogs. 9,10 Similar to those in human patients, all of these injuries cause chronic pain and carry a poor prognosis without costly advanced treatments or surgery. These injuries can lead to retirement from work/athletics and possibly euthanasia in veterinary patients.…”
Section: The Clinical Importance Of Tendon and Ligament Bioreactorsmentioning
confidence: 99%
“…These injuries can lead to retirement from work/athletics and possibly euthanasia in veterinary patients. 9,11,12 Tendons and ligaments are indispensable for stability and motion of the musculoskeletal system, but our understanding of the biology of their development and diseases is incomplete. Tendons transmit the force of muscle to bone across a joint, and thereby facilitate movement and joint stabilization.…”
Section: The Clinical Importance Of Tendon and Ligament Bioreactorsmentioning
confidence: 99%
“…In contrast, diagnostic ultrasound allows for increased ease of acquisition without the need for sedation or anesthesia, and the ability to make contralateral comparisons. An ability to evaluate the contralateral limb may be particularly valuable in dogs with bilateral forelimb lameness, reported in up to 37.6% of dogs with a supraspinatus tendinopathy ( 10 ), making diagnostic ultrasound a convenient modality for both patient diagnosis and an evaluation of patient response to treatment over time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports on the treatment of ST in dogs have included both conservative and surgical management ( 26 – 30 ). While both surgical management and conservative management have been reported for treatment of ST in dogs, up to 55% of surgically treated dogs and in up to 33% of non-surgically treated dogs have persistence or recurrence of lameness ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…While both surgical management and conservative management have been reported for treatment of ST in dogs, up to 55% of surgically treated dogs and in up to 33% of non-surgically treated dogs have persistence or recurrence of lameness ( 26 , 27 ). Regarding conservative medical management, our retrospective study on 327 ST cases in dogs revealed 75% failed to respond to rest and non-steroidal anti-inflammatory drugs and 40% failed to respond to a dedicated rehabilitation therapy program ( 30 ). Recent studies have suggested the potential efficacy of biologic regenerative therapies in humans ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%